Global poverty, justice and law = Küresel fakirlik, adalet ve hukuk - Shuaib, Farid Sufian (2016)
Poverty means lack of basic capacity to participate effectively in society and not having enough to feed and to clothe. This paper looks at definition of poverty at the world level and then considers the position in Malaysia. The paper connects the phenomenon of poverty with the concept of justice and how international law and Malaysian law regards poverty and efforts to eradicate poverty. The paper will also looks at the steps taken in Malaysia to assist poor community and assistance rendered to alleviate poverty.